Francisco Rodríguez Adrados, Del teatro griego al teatro de hoy, Madrid, Alianza Editorial, 1999, 369 pp. (Minerva, 2019)
Review: Francisco Rodríguez Adrados, Del teatro griego al teatro de hoy, Madrid, Alianza Editorial, 1999, 369 pp.